Development And In Vivo In Vitro Characterizations Of Timolol Maleate In-Situ Gels - K. S. RATHORE (International Journal of Pharma and Bio Sciences, 2011)
Ocular drug delivery is one of the most fascinating and challenging endeavours facing the research world of pharmaceutics. The poor uptake of many ocular drugs is mainly due to the rapid elimination process by tear turnover. A prolonged precorneal residence time would result in higher absorption for some drugs, a prolonged duration of their therapeutic effect. Recently, in-situ gel formulations have extensively been studied to enhance ocular bioavailability and duration of the drug therapy. It is known that in-situ gels are retained better in the eye than the conventional ocular dosage forms like eyedrops as solutions and suspensions. The phase-change polymers which trigger the drug release in response to external stimuli are the most investigated in controlled drug delivery. Various polymers undergo sol-gel transition due to physical (temperature) or chemical (pH, ions) stimuli when instilled into cul-de-sac of eye. The present work describes the formulation and evaluation of an in-situ ocular delivery system of an antiglaucomatous agent, timolol maleate, which is used in the treatment of primary open angle glaucoma, based on pH-triggered gelation. Poly acrylic acid was used as the gelling agent in combination with hypromellose, which acted as a viscolyzer. The developed formulation was therapeutically efficacious, non-irritant, stable and provided sustained release of the drug over a long period and shelf-life determined by Arrhenius equation was 1.6 years. Intra ocular pressure determined with Schiotz tonometer and eye irritation. study. conducted on albino rabbits by Draize technique. The developed system is thus a viable alternative to conventional formulations.